Teenage motherhood: Its relationship to undetected learning problems. - Rauch-Elnekave H (Adolescence)
This study describes characteristics of a group of 64 adolescent mothers and their infants who participated in a program for teenage mothers run by a local health department. A majority of the girls for whom California Achievement Test (CAT) scores were available scored one or more years below grade level in reading and in language skills. Relative delays in infant development (language and social domains) were also documented. High levels of self-esteem as well as general social acceptance (by adults and peers) of early out-of-wedlock parenting suggest that early motherhood may represent an alternative avenue to experiencing success for girls who are having academic difficulties. These findings, which suggest the likelihood of a high incidence of undetected learning problems in this population, indicate that these difficulties may have a significant relationship to the high rate of school dropout associated with adolescent motherhood. The findings bring into question the notion of 'unintended pregnancies' and the wisdom of current federal policies for preventing adolescent parenthood that rely on the promotion of abstinence.